Media Pembelajaran Jenis Jamur Berbasis Augmented Reality Menggunakan Metode Marker Based Tracking - Tedi Wardiana; Eka Wahyu Hidayat; Euis Nur Fitriani Dewi (Jurnal Teknologi Informasi dan Multimedia, 2025)
Mushrooms are a plant-based food source with considerable potential and are often found around us. However, some types of mushrooms have similar characteristics and morphology. Based on these problems, an application is made that aims as a medium for the introduction of mushroom types through the use of Augmented Reality (AR) technology. By utilizing Augmented Reality as an interactive educational media, it is expected to facilitate users in obtaining information about the type of fungus accompanied by visualization in the form of 3D objects. The research method used consists of three stages, namely data collection, multimedia product creation, and evaluation. This mushroom type learning application is made using AR marker based on tracking technology with the MDLC (Multimedia Development Life Cycle) method according to Luther Sutopo. Based on the results of Black Box testing, angle, distance and light intensity testing, the application can function properly. Evaluation using the System Usability Scale (SUS) was conducted on the general public with an age range of 17-45 years in RW 05 Panyingkiran Village, Indihiang District, Tasikmalaya City with a population of 356 people, determining the number of respondents using the slovin formula which is 32 people. The test results show that the application obtained an average score of 74.78, which indicates that the application is in the “Acceptable” category for Acceptability Range, Grade C in Grade Scale, and “Good” in Adjective Rating.